Open Science Indicators as Metadata Fields? - Fradkin, Chris; Mugnaini, Rogério (Frontiers in Research Metrics and Analytics, 2021)
Since 2000, there has been qualitative growth in the field of scientometrics. Innovations such as the DOI and the ORCID have irrevocably changed the scientific landscape. They have enabled analyses previously unheard of, in the decades preceding the new millennium. This paper proposes open science indicators (open data, open material, preregistration) as article-specific metadata fields. The authors reference the history of funding information, from bare acknowledgements to metadata field. The authors describe the mission of the Center for Open Science, and its TOP Factor database, as well as the performance of open science badges. Possibilities for a pilot study are explored, with an acknowledgement of the complexity of this undertaking.